Developing robust, hydrogel-based, nanofiber-enabled encapsulation devices (NEEDs) for cell therapies. (January 2015) - An, Duo; Ji, Yewei; Chiu, Alan; Lu, Yen-Chun; Song, Wei; Zhai, Lei; Qi, Ling; Luo, Dan; Ma, Minglin
Abstract: Cell encapsulation holds enormous potential to treat a number of hormone deficient diseases and endocrine disorders. We report a simple and universal approach to fabricate robust, hydrogel-based, nanofiber-enabled encapsulation devices (NEEDs) with macroscopic dimensions. In this design, we take advantage of the well-known capillary action that holds wetting liquid in porous media. By impregnating the highly porous electrospun nanofiber membranes of pre-made tubular or planar devices with hydrogel precursor solutions and subsequent crosslinking, we obtained various nanofiber-enabled hydrogel devices. This approach is broadly applicable and does not alter the water content or the intrinsic chemistry of the hydrogels. The devices retained the properties of both the hydrogel (e.g. the biocompatibility) and the nanofibers (e.g. the mechanical robustness). The facile mass transfer was confirmed by encapsulation and culture of different types of cells. Additional compartmentalization of the devices enabled paracrine cell co-cultures in single implantable devices. Lastly, we provided a proof-of-concept study on potential therapeutic applications of the devices by encapsulating and delivering rat pancreatic islets into chemically-induced diabetic mice. The diabetes was corrected for the duration of the experiment (8 weeks) before the implants were retrieved. The retrieved devices showed minimal fibrosis and as expected, live and functional islets were observed within the devices. This study suggests that the design concept of NEEDs may potentially help to overcome some of the challenges in the cell encapsulation field and therefore contribute to the development of cell therapies in future.